KERJA SAMA PEMERINTAH KABUPATEN BANJARNEGARA DENGAN BALAI PELESTARIAN CAGAR BUDAYA PROVINSI JAWA TENGAH DALAM PENGELOLAAN DAN PELESTARIAN KAWASAN CAGAR BUDAYA DATARAN TINGGI DIENG TAHUN 2014-2018 - Faa’iz Oktavian Lestyono; Muhammad Adnan (Journal of Politic and Government Studies, 2019)
In the era of autonomy, each region is required to responsible for the refineries and the preservation of cultural heritage, one of them by way of cooperation between government agencies or the private sector. However, cooperation in the preservation of buildings and cultural heritage area that often clash with economic interests. If more priority to economic interests and the exclusion of buildings of cultural heritage, not cultural heritage buildings will be converted into agricultural land or popping new buildings that are more economically profitable. Therefore this research aims to determine how the process of cooperation between the Government of Banjarnegara Regency with the institute for Preservation of Cultural Heritage of Central Java Province in the Management and Preservation of The Cultural Heritage of the Dieng Plateau years 2014-2018.This research uses descriptive qualitative research methods with the documentation and interviews as data collection techniques. The target in this research is the government of Banjarnegara Regency, the institute for Preservation of Cultural Heritage of Central Java Province, and community within Cultural Heritage Area. Partnership is a form of partnership cooperation between two or more parties that aims to improve the ability of an organization in achieving its objectives. Based on the results of the research as a whole that working together in the management and preservation of The Cultural Heritage of the Dieng Plateau have already given positive results, as evidenced by a well-ordered environment of street vendors, which is neat, making of the flower garden Kalalili around the Area of Cultural Heritage, the availability of central park for buses, increasing the number of toilets and litter bins.Keywords: Cooperation, Management, Preservation, Cultural Heritage, Dieng Plateau,Banjarnegara.